GIS-material for the archaeological project: Fivelstad 61 - Stiftelsen Kulturmiljövård Mälardalen (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Stiftelsen Kulturmiljövård Mälardalen (KM) performed a field evaluation of the ancient monument RAÄ 61 in Fivelstad parish, Motala municipality, Östergötland, during April-May 2009. The background for the survey was the Swedish Road Administration's proposed new construction and reconstruction of National Road 32/50 between Motala and Mjölby. In a previous evluation in the western part of RAÄ 61, a cultural layer or cultivation layer that superimposed several features was found, including a hearth and a post hole.The post hole has been dated to the Early Bronze Age. The field evaluation shows that this layer continues to the east. In the southern part of the investigation area three hearths were revealed, which may be part of a hearths area. One of these hearths have been dated to the transition between the Bronze Age and Early Iron Age. All artefacts and most of the features were found in an area that is partially destroyed as a result of ploughing in recent times. The best-preserved features can be expected in areas with preserved cultural or older cultivation layers under the topsoil. KM has therefore proposed two areas to be subject to excavation: one related to the cultural/cultivation layers in the north and one covering the presumed hearts area in the south.

Purpose:

The information in the purpose is translated from the archeological report:
The field evaluation was prompted by the Swedish Road Administration's proposed new construction and reconstruction of National Road 32/50 between Motala and Mjölby. The purpose of the evaluation was to provide input to the County Administrative Board's permission assessment, and the Swedish Road Administration's further planning.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Stiftelsen Kulturmiljövård Mälardalen (KM) utförde under april-maj 2009 en arkeologisk förundersökning av fornlämning 61 i Fivelstads socken, Motala kommun, Östergötland. Bakgrunden för undersökningen var Vägverkets planerade ny- och ombyggnad av Riksväg 32/50 mellan Motala och Mjölby. I samband med en tidigare förundersökning inom västra delen av Fivelstad 61 framkom bland annat ett kulturlager eller äldre odlingslager som överlagrade flera anläggningar, bland annat en härd och ett stenskott stolphål. Stolphålet har daterats till äldre bronsålder. Förundersökningen visar att detta lager fortsätter mot öster. I södra delen av förundersökningsområdet framkom tre härdar som kan utgöra delar av ett härdområde. En av dessa härdar har daterats till övergången mellan bronsålder och äldre järnålder. Alla fynd och de flesta anläggningarna framkom i ett område som delvis är förstört som följd av plöjning i nyare tid. De bäst bevarade anläggningarna kan därför förväntas i områden med bevarade kultur- eller äldre odlingslager under dagens ploglager. KM har därför föreslagit att två områden blir föremål för särskilda undersökningar: ett i anslutning till kultur-/odlingslagret i norr och ett som omfattar det förmodade härdområdet i söder.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Den arkeologiska förundersökningen föranleddes av Vägverkets planerade ny- och ombyggnad av Riksväg 32/50 mellan Motala och Mjölby. Syftet med förundersökningen var att skapa ett underlag för länsstyrelsens tillståndsbedömning, samt Vägverkets vidare planering.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.

Förundersökningen genomfördes genom sökschaktning med maskin. Totalt grävdes 30 schakt (1 377 löpmeter). Schakten var 10-42 meter långa och huvudsakligen runt tre meter breda. Ett schakt utvidgades till närmare tio meters bredd (schakt 2723) för att utreda omfattningen av anläggningar i detta område. Alla schakt lades igen efter avslutad undersökning.
GIS-material för arkeologiskt projekt: Fivelstad 61
Keywords: Bronze Age; bronsålder; Iron Age; järnålder; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi